Физические модели обратимых отказов полупроводниковых приборов в условиях электромагнитного воздействия - Кравченко, Владимир Иванович; Серков, Александр Анатольевич; Бреславец, Виталий Сергеевич; Яковенко, Игорь Владимирович (НТУ "ХПИ", 2015)
Предложены физические модели появления обратимых отказов полупроводниковых приборов в условиях воздействия электромагнитного излучения. Разработан новый механизм появления поверхностных электронных состояний на неровной поверхности проводящих твердых тел. Определены механизмы возникновения неустойчивостей собственных колебаний полупроводниковых сверхрешеток, обусловленных их взаимодействием с потоками заряженных частиц в условиях влияния внешнего электромагнитного излучения. Показано, что влияние импульсного электромагнитного излучения сопровождается возникновением токов в проводящих элементах изделий и возникновением их внутренних полей. Исследовано влияние неоднородных свойств поверхностей проводящих твердых тел в излучающих структурах на спектральные характеристики переходного и черенковского излучения. Разработана теория бесстолкновительного затухания поверхностных поляритонов в квантовом и классическом приближениях.

A new mechanism of initiation of surface at uneven of the conducting solid bodies is proposed. The development of theory of interaction of mi-crowave electromagnetic oscillations and charged particles in bounded plasma-like media and the study of kinetic and hydrodynamic beam instabilities in solid – like structures applied in the present microwave electronics is proposed. The power losses of the flow of charged particles caused by such an interaction due to excitation of surface polaritons in the semiconductor superstructure have been determined. The influence of pulsed electromagnetic radiation on electric radio apparatus is often accompanied by currents arcsing on inner current – conducting elements as well as by the distortion of their internal fields. A theory of collisionless damping of surface plasmas in quantum and classical approcsimations is elaborated and the conditions of its conversion are determined. The effect of inhomogeneouse properties of surface of open radiating structures on the spectral characteristics of transition radiation is studies. It is found that the energy losses related to excitation of volume helicons are equivalent to the energy losses of a magnetic moment created due to the charge rotation. New mechanism of excitation of surface magneto plasmas of oscillations by the moving radiation source is suggested.
Physical models of reversible refusals of semi-conductor devices under an electromagnetic
Keywords: колебания; плазма; сверхрешетки; безстолкновительное угасание; генерирование; oscillations; plasma; collisionless extinction